Efficacy of PVC coated fabric bag for on-farm storage of wheat (Triticum aestivum) - KUMAR, SUNIL; MOHAPATRA, DEBABANDYA; KOTWALIWALE, NACHIKET; SINGH, KRISHNA KUMAR (The Indian Journal of Agricultural Sciences, 2019)
A PVC coated fabric bag was evaluated for on-farm storage of wheat for 8 months without fumigation. It was compared with fumigated samples stored in a metal bin. Temperature, relative humidity (RH) and carbon dioxide (CO2) of the bag and surroundings were monitored throughout the storage period. The interstitial temperature, RH and CO2 in bag were in the range of 15.2–37.7°C, 28.5–40.6% and 406–5764 ppm respectively. After 2 months of storage, no significant difference was observed between the quality parameters of samples stored in both structures; however, at the end of 8 months of storage, thousand kernel weight (57.8 g), mold count (39.8×101 CFU/g), moisture content (10.7%), besatz (5.3%) and bored grain (1.6%) were significantly higher in the bag samples compared to the control samples, whereas germination percentage was reduced to 76.7% from 96.7% in bag. Nevertheless, the quality of grain was within the acceptable consumable quality limit as per codex standards due to bored grains less than 1.5% for 6 months in bag.